Perbandingan Performa Antara Treatment Hydrochloric Acid dan Carboxylic Acid Terhadap Kenaikan Produksi pada Sumur Minyak Berat - Itsnaini, Hafizh; Sunarno, Sunarno; Padil, Padil (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
Duri steam flood is the largest hot steam injection project in Indonesia, facing challenges in preventing production declines. Objective project is showed decrease in production due to crustal deposition (scale). The Stiff and Davis method shows a Stability Index of 1.43, with a tendency for scale formation, especially CaCO3, in accordance with the Ryznar method. Increasing the production of x, yz layer wells in the Duri field, designing acidification stimulation with a pumping pressure of 400 psi, an injection rate of 2 bbl/minute and an acid volume of 600 gallons, after that comparing the performance of hydrochloric acid and carboxylic acid. Analysis showed that hydrochloric stimulation resulted in a significant increase in production of 115 BFPD / 8 BOPD (42% increase), while carboxylate stimulation showed a slower increase of 40 BFPD / 3 BOPD (24% increase). An economic evaluation shows chloride acidification produces an annual NPV gain of $48,002, compared to carboxylate acidification with an annual NPV gain of $22,554. Thus, chloride acidification proved to be economically profitable for the x, yz layers in the Duri field. This study highlights optimal acid stimulation strategies to mitigate scale-related production challenges in steam flood projects.